Move Analysis of Thesis and Dissertation Abstracts in One Philippine Graduate Institute - Allen Dave Briones Arboleda (Universitas Muhammadiyah Metro, 2022)
In the Philippines, move-analytic investigations have been carried out. However, none of these have attempted to look into the genre of thesis and dissertation abstracts. Cognizant of this gap, this study examined a corpus of 100 research abstracts written by Filipino graduate students in one private university in Western Metro Manila. In order to identify the moves, rhetorical organization, linguistic features, and deviations in the corpus, mixed-method research design was employed. Analyses of data reveal that all the moves in Hyland’s model are present in the corpus. Such moves are linguistically realized through the use of present tense, present perfect tense, attitudinal stance words, deictic item+ inquiry type noun+ reporting verb formulaic pattern, past-passive constructions, opening subject+ reporting verb+ that-complement clause formulaic pattern, modals, and nominal phrases. As to rhetorical organization, non-linear organization is the most preferred, while linear organization is the least. With respect to deviations, word count, format, level of usage, syntactic structure, mechanics, grammar, and lexis are uncovered. Based on the results obtained, it is deduced that thesis and dissertation abstracts as corpus can provide meaningful insights as regards the exploration of moves vis-à-vis their linguistic realizations and sequences, academic writing, and Philippine English.